Influence of total running experience on lower leg variability: implications for control and performance in male athletes - Steele, J.; Hunter, I. (Sports, 2025)
This study investigates the relationship between total running experience, defined as cumulative years of running multiplied by weekly mileage, and variability in lower leg joint kinematics during treadmill running. Twenty-seven male athletes participated, running while kinematic and kinetic data were collected. Linear regression revealed significant negative correlations between total running experience and variability in both knee and ankle joint range of motion (ROM). Specifically, ankle ROM variability (p = 0.001, R2 = 0.35) and knee ROM variability (p = 0.002, R2 = 0.32) were reduced in runners with more experience. A stepwise regression model further identified ankle ROM variability as a significant predictor (p = 0.033), explaining 44.25% of the variance in total running experience. A significant positive correlation between running experience and instantaneous vertical loading rate (IVLR) (p = 0.025, R2 = 0.15) suggests that more experienced runners generate higher load rates. These findings indicate that more experienced runners exhibit more consistent and stable movement patterns, reflecting refined motor control. The results support the hypothesis that greater running experience is associated with reduced variability in movement patterns within a controlled environment, providing insights into the mechanisms that could contribute to enhanced performance and injury prevention.